2019
DOI: 10.3390/ijerph16091613
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stressful Events on Motivations, Self-Efficacy, and Development of Post-Traumatic Symptoms among Youth Volunteers in Emergency Medical Services

Abstract: During the last decades, Israeli emergency medical services (EMS) personnel has been exposed to different potentially traumatic events, including mass terror attacks. The aims of the present study were to identify how potentially traumatic events affect young volunteers in their motivation to volunteer and their perceived self-efficacy while being at risk of developing post-traumatic symptoms. The final sample included 236 Magen David Adom (MDA, the "Israeli Red Cross") youth volunteers. The study evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…As recent studies suggest, the relevance of social motives for Generation Zs seems less influencing on their attitudes towards volunteering [53]. These findings seem to support the idea that social and growth motivations both have a more pronounced impact on the outcomes for older than for younger people, accordingly to recent research on the impact of stress on youth volunteers [54].…”
Section: Discussionsupporting
confidence: 64%
“…As recent studies suggest, the relevance of social motives for Generation Zs seems less influencing on their attitudes towards volunteering [53]. These findings seem to support the idea that social and growth motivations both have a more pronounced impact on the outcomes for older than for younger people, accordingly to recent research on the impact of stress on youth volunteers [54].…”
Section: Discussionsupporting
confidence: 64%
“…Drawing on the self-determination approach, this means possessing an autonomous self and not depending on unstable achievements or conditional approval. Consistently, previous research has indicated that volunteers’ resilience may benefit from a sense of self-efficacy [ 52 ], psychological endurance, and organization support [ 16 , 17 ]. All these characteristics may be targeted for intervention.…”
Section: Discussionsupporting
confidence: 68%
“…As with professionals, not only may volunteers be exposed to the negative consequences of dealing with human trauma, but their activity could also be an opportunity for satisfaction and growth. For instance, an increased sense of self-efficacy has been detected after participating in stressful events [3]. Moreover, [20] found that volunteers who had participated in potentially traumatic events showed high levels of resilience despite their experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Volunteers play an essential role in different agencies and nonprofit organizations that work for the good of different sectors of the population, hence the interest in identifying the factors that make the management and promotion of volunteering possible [1][2][3]. Research has examined volunteer motivations and other factors (satisfaction, integration in the organization, perceived self-efficacy, etc.…”
Section: Introductionmentioning
confidence: 99%